Electrofacies in gas shale from well log data via cluster analysis: A case study of the Perth Basin, Western Australia - Karimian Torghabeh, A.; Rezaee, M. Reza; Moussavi-Harami, R.; Pradhan, B.; Kamali, M.R.; Kadkhodaie-Ilkhchi, A. (Versita, co-published with Springer Verlag, 2014)
Identifying reservoir electrofacies has an important role in determining hydrocarbon bearing intervals. In this study, electrofacies of the Kockatea Formation in the Perth Basin were determined via cluster analysis. In this method, distance data were initially calculated and then connected spatially by using a linkage function. The dendrogram function was used to extract the cluster tree for formations over the study area. Input logs were sonic log (DT), gamma ray log (GR), resistivity log (IND), and spontaneous potential (SP). A total of 30 reservoir electrofacies were identified within this formation. Integrated geochemical and petrophysics data showed that zones with electrofacies 3, 4, 9, and 10 have potential for shale gas production. In addition, the results showed that cluster analysis is a precise, rapid, and cost-effective method for zoning reservoirs and determining electrofacies in hydrocarbon reservoirs.